bahasa inggris: Bahasa Indonesia - Rony Wirachman; Ike Kurniawati (Universitas PGRI Adi Buana Surabaya, 2023)
The achievement of learning objectives in forming quality educated human beings includes intelligence in cognitive, affective and psychomotor aspects. Intelligence is divided into three pillars namely Intelligence Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ). The pillars certainly have different meanings. Individuals who have a better EQ will be more successful in the world of work later, successful learning is the achievement of national education goals. The reality in the field based on observations and interviews is the use of learning models that are not based on social learning theory, and students' creativity is not visible in learning activities. This research uses a qualitative approach with a descriptive study type with the literature study method. The purpose of this study is to contribute insightful knowledge to educational experts and educational practitioners about the concept and implementation of role playing learning models based on social learning theory